1235 A Multi-Site Review of Second Hip Fractures Across 6 Dublin Teaching Hospitals. (12th October 2021) - Murphy, B; Downey, C; Flannery, S; Daly, T; Conway, S; Gaffar, M; Dawson, P; Collins, D; Kenny, P; McCarthy, T; Cashman, J; Hurson, C; et al.
Abstract: Introduction: Hip fractures are a common presentation to Irish hospitals with 3, 701 hip fractures recorded by 16 hospitals in the Irish Hip Fracture Database (IHFD) in 2019. Second hip fractures (HF2) make up a significant proportion of hip fractures and represent an opportunity to prevent subsequent fragility fracture. Method: Hip fracture datasheets from 2019 in six Dublin hospitals were analysed. Results: 1, 284 hip fractures in total were recorded in 2019 in these six hospitals. 112 of these were second hip fractures (8.72%). 24.1% of patients had a HF2 in year 1 post their first hip fracture (HF1). 14.3% of patients had a HF2 in Year 2, 8% in Year 3, 8.9% in Year 4 and 6.3% in Year 5. 17.9% of patients had an HF2 at an unknown time in relation to their HF1. 57.6% of all patients with any hip fracture were started on bone protection medications (BPMs) during their admission. 18.9% continued a pre-admission prescription. 7% of all patients were previously assessed and determined not to require BPM. 6.9% of patients were awaiting outpatient department (OPD) assessment for bone protection. 8.6% had no assessment for bone protection conducted. Of all patients with an HF2, 48.2% were started on BPMs on admission with their HF2. 33% continued BPMs started pre-admission. Discussion: In 2019, approximately 1 in 10 hip fractures were second hip fractures. Evidence suggests that fracture liaison services represent a viable, economic means of preventing second hip fractures to improve patient outcomes and reduce healthcare expenditure.